2023
DOI: 10.3390/toxics11070610
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Transcriptome Analysis on the Leaves of Rosa chinensis Jacq. under Exposure to Polycyclic Aromatic Hydrocarbons

Abstract: The leaves of plants can be recommended as a cheap and sustainable environmental protection tool to mitigate PAHs with high toxicity in the ambient environment because they can serve as a reactor to remove ambient PAHs. Although previous studies have demonstrated that PAHs exhibit toxicological features, our knowledge about how ambient PAHs influence the leaves of plants is limited regarding the leaves of plants reducing ambient PAHs as a reactor. In this study, 1-year-old Rosa chinensis Jacq. with good growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Some prior studies have shown that leaves can uptake water-soluble brown carbon and different amino acids via stomata within 30 min serving as nutrients to maintain growth [32][33][34][35]. Our prior study also examined the interaction process between the polycyclic aromatic hydrocarbons (PAHs) at high concentrations and tree leaves using whole-transcriptome analysis [36]. Based on the analysis of the significant differentially expressed genes, seven main pathways play roles in absorbing high concentrations of PAHs on the surface of plant leaves [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some prior studies have shown that leaves can uptake water-soluble brown carbon and different amino acids via stomata within 30 min serving as nutrients to maintain growth [32][33][34][35]. Our prior study also examined the interaction process between the polycyclic aromatic hydrocarbons (PAHs) at high concentrations and tree leaves using whole-transcriptome analysis [36]. Based on the analysis of the significant differentially expressed genes, seven main pathways play roles in absorbing high concentrations of PAHs on the surface of plant leaves [36].…”
Section: Introductionmentioning
confidence: 99%
“…Our prior study also examined the interaction process between the polycyclic aromatic hydrocarbons (PAHs) at high concentrations and tree leaves using whole-transcriptome analysis [36]. Based on the analysis of the significant differentially expressed genes, seven main pathways play roles in absorbing high concentrations of PAHs on the surface of plant leaves [36]. Consequently, the tree leaves could retain the BC on their wax layers [23].…”
Section: Introductionmentioning
confidence: 99%
“…Roses ( Rosa chinensis ) is an important ornamental plant, with economic, cultural, and symbolic significance 15 . They are used not only as fresh cut flowers but also widely used as outdoor landscaping flowers 16 . During the application of outdoor greening, adverse environments such as high temperature and drought are often encountered, which affect its application scope and ornamental quality 17 .…”
Section: Introductionmentioning
confidence: 99%